A new funding model for open-access monographs: Introducing a novel business model and approach to publishing OA books through library membership funding - Eve, Martin; Pinter, Frances (Septentrio Conference Series, 2020)
See RECORDING (starts at 00:40:30). We outline the work of a university press, with assistance from the COPIM Project (Community-led Open Publication Infrastructures for Monographs), in building an innovative revenue model to fund open access monographs at a traditional publisher. Building on library journal subscription models (eg: OLH) and on Knowledge Unlatched’s approach to monograph funding, we present a sustainable OA publishing model that gives members exclusive access to a backlist, with the revenue then used to make the frontlist openly accessible. The model can be emulated by other scholarly presses who wish to take advantage of the opportunities that open access publishing affords. Supporting information: Led by Dr Frances Pinter (Publishing Advisor, & founder of Knowledge Unlatched) and Professor Martin Paul Eve (OLH, Birkbeck & COPIM) the case study explores an innovative revenue model that will transition new titles at a well-known publisher to a viable open-access model. COPIM is an international partnership of researchers, universities, librarians, publishers and infrastructure providers working on bringing about a new OA publishing ecosystem. Their remit is to build a revenue infrastructure, and examine production workflows and metadata, experimental publishing and archiving. The project is working with colleagues across the sector to document existing and potential ways of funding open-access monographs and is consulting with academics, publishers, libraries, funders, and policy makers. The publisher case study aims to initiate and document a ‘working model’ as the next step in creating a practical toolkit and roadmap for other publishers.